Genetic Stability Assessment of Three Tomato Hybrids (Lycopersicon esculentum) grown in the Libyan Green Mountains Using SRAP and RAPD Techniques - Emsaed, Amani; Elkagkheg , Abdelrezk; Elmeer , Khaled (Scientific Journal of University of Benghazi, 2024)
The genetic diversity of F1 tomato hybrid (Nada, Mona, and Dania) grown in Libyan Green Mountain (LGM) was investigated using SRAP and RAPD molecular marker techniques while the coefficient of variation C.V was used to investigate F1 seed purity. The coefficient of variation C.V., in the three cultivars Nada, Mona and Dania are 31.88, 51.66 and 44.18, respectively, indicating the homogeneity of Nada cultivar over Dania and Mona. The SRAP marker provided a total number of 29 amplified DNA bands with an average of 9.67 bands per primer, 26 of which were polymorphic (67% polymorphism), while the RAPD marker provided a total of 73 bands with an average of 14.6 bands per primer; all of them were 100% polymorphic. The genetic diversity for the three studied cultivars was 0.31, whereas Nada cultivar was the most homogeneous recording a genetic diversity of 0.24 compared with Mona 0.25 and Dania 0.28 Dania. Principal coordinate analysis (PcoA) divided tomato F1 hybrid samples into two main groups, the first (A) includes all the plants of a Nada hybrid cultivar, while group (B) consists of overlapping of Dania and Mona cultivars, reflecting the genetic relatedness.